Representasi Makna Rahmat Pada Lirik Lagu “Rahmatun Lil’alameen” Karya Maher Zain (Kajian Semiotika) - Rahim, Muhammad; Fikri; Hudri, Mawaddah (Diwan Media Pustaka, 2023)
This article aims to analyze meaning of mercy in the song “Rahmatul Lil’alameen” by Maher zain with the Roland Barthes’s semiotics theory. Barthes stated in his theory that meaning have three meanings namely, denotation, connotation and myth. Those meanings used to represent meaning of mercy that implied in the song. The research approach in this research uses a qualitative method approach. This approach used to represent and explain deeper about study of meaning as research object. Data collection using observation techniques. The researcher listened to the song carefully, then noted the words that had the meaning of grace. The data that has been recorded is then analyzed based on the semiotic theory of Roland Barthes. The research results show that the denotational meaning of the lyrics of the song